MashupOS: Operating System Abstractions for Client Mashups - Howell, Jon; Jackson, Collin; Wang, Helen, Xiaofeng Fan (Hot Topics in Operating Systems (HotOS), 2007)
Web browser support has evolved piecemeal to balance the security and interoperability requirements of client-side script services. This evolution has led to an inadequate security model that forces Web applications to choose between security and interoperation. We draw an analogy between Web sites’ sharing of browser resources and users’ sharing of operating system resources, and use this analogy as a guide to develop protection and communication abstractions in MashupOS: a set of abstractions that isolate mutually-untrusting web services within the browser, while allowing safe forms of communication.